Thyroid dysfunction and amiodarone - Lima, J (2013)
Although most patients remain clinically euthyroid, some develop amiodarone-induced hyperthyroidism (HPEAI) or hypothyroidism (HPOAI). The authors present a retrospective analysis of ten patients with amiodarone-induced thyroid dysfunction. Six patients were female and mean amiodarone intake was 17.7 months. HPOIA was more common (six patients). From all the patients with HPEAI, two had type 2, one had type 1, and one had type 3 hyperthyroidism. Symptoms suggestive of thyroid dysfunction occurred in five patients, most of them with HPOAI. In HPEAI, the most frequent symptom was exacerbation of arrhythmia (three patients). Discontinuation of amiodarone and treatment with levothyroxine was chosen in 83.3% of the HPOAI cases, while thyonamide treatment with corticosteroids and without amiodarone was the option in 75% of the HPEAI cases. There were three deaths, all in patients with HPEAI. HPEAI is potentially fatal. The clinical picture may be vague, so the thyroid monitoring is mandatory.